Ballers. The complete fourth season [videorecording (DVD)] - Levinson, Stephen (Ballers (Television program), 2019)
Spencer is back in a new season of the hit comedy that explores the glamorous, and often cutthroat, world of pro football, as seen through a group of past and present players striving to stay in the game.